PENGARUH PENDAPATAN ASLI DAERAH, LEVERAGE, DAN INTERGOVERNMENTAL REVENUE TERHADAP KINERJA KEUANGAN PEMERINTAH DAERAH - Thassha Amalia (2017)
The purpose of this study was conducted to examine the effect of local revenue, leverage, and intergovernmental revenue toword local governments financial performance in district / municipalities in East Java. The population in this study are 38 district / municipalities in East Java already has a data realization revenue budget expenditure and balance sheet in the periode 20112015. The Sampling technique is purposive sampling method which results for 34 samples in 2011-2015. The Test of local revenue variable, Leverage variable, and Intergovernmental revenue variable on Local Governments Financial Performance using multiple linear regression models. Simultaneously, the result showed that the local revenue, leverage, and intergovernmental revenue significant influence on local governments financial performance. partially, the result showed that the local revenue a significant influence on local governments financial performance. While variable of leverage had no influence on local governments financial performance. Intergovernmental revenue variable had no influence on local governments financial performance.